2018
DOI: 10.3389/fphar.2018.01249
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Herbal Medicines for Digestive System Malignancies

Abstract: Herbal medicines, as an important part of traditional Chinese medicine (TCM), have been used to treat digestive system malignancies (DSM) for many years, and have gradually gained recognition worldwide. The role of herbal medicines in the comprehensive treatment of DSM is being improved from adjuvant treatment of the autologous immune function in cancer patients, to the treatment of both the symptoms and disease, direct inhibition of tumor cell growth and proliferation, and induction of tumor cell autophagy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 165 publications
0
9
0
Order By: Relevance
“…In addition, it has been elucidated that the anti-tumor mechanisms of TCM involve the regulation of autologous immune function, inhibition of tumor cell growth and proliferation, and induction of tumor cell autophagy and apoptosis. [10][11][12] According to accumulated evidenced-based data, the combination of Chinese herbal injections (CHIs) and chemotherapy or radiotherapy is associated with considerable efficacy in treating patients with digestive system malignancies. [13][14][15] However, a paucity of scientific research exists regarding the combined use of CHIs plus chemotherapy in patients with EC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been elucidated that the anti-tumor mechanisms of TCM involve the regulation of autologous immune function, inhibition of tumor cell growth and proliferation, and induction of tumor cell autophagy and apoptosis. [10][11][12] According to accumulated evidenced-based data, the combination of Chinese herbal injections (CHIs) and chemotherapy or radiotherapy is associated with considerable efficacy in treating patients with digestive system malignancies. [13][14][15] However, a paucity of scientific research exists regarding the combined use of CHIs plus chemotherapy in patients with EC.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) found that different concentrations (125, 250, and 500 μg/ml) of the methanolic extracts of B. aristata could significantly inhibit cell migration and induce apoptosis in human breast cancer cells (MCF-7). Berberine and palmatine are isoquinoline alkaloids ( Figure 3 ), which can be extracted from some medicinal plants, such as Berberis aristata , B. kansuensis , B. diaphana , B. vernae , and Coptis chinensis ( Serasanambati et al., 2015 ; Li et al., 2018b ; Neag et al, 2018 ; Sheng et al., 2018 ). Berberine exhibits multiple biologic effects with low toxicity, and the antitumor activities in various human cancer cells have been reported ( Yip and Ho, 2013 ; Zhao et al., 2017 ; Yao et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hedyotis diffusa Willd (Baihuasheshecao) which was recorded in Chinese Pharmacopoeia, had the effects of clearing heat and promoting diuresis. In vivo and in vitro studies [23] have shown that Hedyotis diffusa Willd (Baihuasheshecao) improved the digestive tumor remission. Codonopsis pilosula (Franch.)Nannf.…”
Section: Interventionsmentioning
confidence: 99%